A Survey for Examining the Effects of COVID-19 and Infection Control Measures in Older Persons With Mild Cognitive Impairment and Dementia and Their Caregivers - Porcari, Desirée E.; Palmer, Katie; Spalletta, Gianfranco; Ciullo, Valentina; Banaj, Nerisa (Frontiers in Psychiatry, 2020)
Background: During the first wave of the COVID-19 pandemic, many non-urgent outpatient services in Italy were closed due to the Government-enforced lockdown period. So far, little is known about what effect the pandemic, quarantine measures, and reductions in medical services had on people with cognitive impairment and their caregivers. Objectives: To develop two versions (i.e., patients and informants/caregivers) of a survey designed to assess the impact of the COVID-19 pandemic during the first Italian lockdown period (11 March −4 May 2020) on Memory Clinic outpatients with Mild Cognitive Impairment (MCI) or dementia, and their caregivers. Design: Psychiatrists, neuropsychologists, and epidemiologists developed two versions: one for patients with Mild Cognitive Impairment and other cognitive disorders, the other for their relatives and/or caregivers. Each version of the survey includes five sections: (a) socio-demographic information and access to technology devices; (b) individual COVID-19 protection methods; (c) knowledge about COVID-19; (d) the effect of COVID-19 on daily life; and (e) the effect of COVID-19 on emotional state. Conclusion: Until an effective vaccine is developed it is likely that future waves of COVID-19 will result in shielding of vulnerable older adults. We believe that this instrument will be useful as a tool to collect information and help clinicians to promptly respond to changes in patients' cognitive, psychiatric, and somatic health needs, and to help for future planning in possible subsequent quarantine periods.